(untitled) (CAHIERS MAGELLANES-NS, 2024)
The right to health is basically a human right which means that everyone has the right to the highest attainable standard of physical and mental health. For attaining right to health, a clean and fresh environment is the basic need of a person. People consider right to smoke as their fundamental right to live life with leisure but, on the other hand the Constitution of India is perhaps one of the rare Constitutions of the world which contains specific provisions relating to environmental protection. Besides individual health problems, smoking is an environmental pollutant and environmental protection is an individual’s fundamental duty too. Thereby, restricting smoking in public places, we secure few of the rights of non-smokers and contribute to environmental protection. Hence, the above paper provides an insight on the jurisprudence of right to smoke in India and also highlights the health hazards, penal provisions and judicial approach concerning the same.